Bluetooth and wi-fi wireless protocols: A survey and a comparison - De Leon, Gerardo D. (Animo Repository, 2005)
Bluetooth and wi-fi are two communication protocol standards that define a physical layer and a Media Access Control (MAC) layer for wireless communications within a short range. Bluetooth is oriented to connecting close devices, serving as substitute for cables while wi-fi is oriented toward computer-to-computer connections, as an extension or substitute for cabled LANs. For comparison we need to have an overview of their main features such as capacity, network topology, security, QoS support, and power consumption.